Lipoprotein(a) in atherosclerotic cardiovascular disease and aortic stenosis: a European Atherosclerosis Society consensus statement - Kronenberg, Florian; Mora, Samia; Stroes, Erik S G; Ference, Brian A; Arsenault, Benoit J; Berglund, Lars; Dweck, Marc R; Koschinsky, Marlys; Lambert, Gilles; Mach, François; McNeal, Catherine J; Moriarty, Patrick M; et al. (European heart journal, 2022)
Graphical Abstract Graphical abstract Key points from the 2022 Lp(a) consensus statement. Current evidence demonstrates a causal continuous association in different ethnicities between Lp(a) concentration and cardiovascular outcomes including aortic valve stenosis, but not for venous thrombotic events. A meta-analysis of prospective studies shows that very low Lp(a) levels are associated with increased risk of diabetes mellitus. For clinical practice, Lp(a) should be measured at least once in adults and results interpreted in the context of a patient's absolute global cardiovascular risk, with recommendations on intensified early risk factor management by lifestyle modification. The statement also reviews currently available and future possibilities to specifically lower Lp(a). Abstract This 2022 European Atherosclerosis Society lipoprotein(a) [Lp(a)] consensus statement updates evidence for the role of Lp(a) in atherosclerotic cardiovascular disease (ASCVD) and aortic valve stenosis, provides clinical guidance for testing and treating elevated Lp(a) levels, and considers its inclusion in global risk estimation. Epidemiologic and genetic studies involving hundreds of thousands of individuals strongly support a causal and continuous association between Lp(a) concentration and cardiovascular outcomes in different ethnicities; elevated Lp(a) is a risk factor even at very low levels of low-density lipoprotein cholesterol. High Lp(a) is associated with both microcalcification and macrocalcification of the aortic valve. Current findings do not support Lp(a) as a risk factor for venous thrombotic events and impaired fibrinolysis. Very low Lp(a) levels may associate with increased risk of diabetes mellitus meriting further study. Lp(a) has pro-inflammatory and pro-atherosclerotic properties, which may partly relate to the oxidized phospholipids carried by Lp(a). This panel recommends testing Lp(a) concentration at least once in adults; cascade testing has potential value in familial hypercholesterolaemia, or with family or personal history of (very) high Lp(a) or premature ASCVD. Without specific Lp(a)-lowering therapies, early intensive risk factor management is recommended, targeted according to global cardiovascular risk and Lp(a) level. Lipoprotein apheresis is an option for very high Lp(a) with progressive cardiovascular disease despite optimal management of risk factors. In conclusion, this statement reinforces evidence for Lp(a) as a causal risk factor for cardiovascular outcomes. Trials of specific Lp(a)-lowering treatments are critical to confirm clinical benefit for cardiovascular disease and aortic valve stenosis. Audio Abstract 10.1093/brain/ehac361_audio1 Audio Abstract ehac361media1 6311018000112